ANALISIS KELAYAKAN FINANSIAL USAHATANI JAGUNG DI DESA OTAK RARANGAN KABUAPTEN LOMBOK TIMUR - Septiadi, Dudi; Fadli, Fadli (JURNAL AGRIMANSION, 2024)
This study aims to; (1) analyze the costs and income of corn farming in Otak Rarangan Village, East Lombok Regency; (2) analyze the financial feasibility of corn farming in Otak Rarangan Village, East Lombok Regency. The method used in this study is the descriptive-quantitative method. The unit of analysis in this study was Corn Farmers in Otak Rarangan Village, East Lombok Regency, totaling 30 respondents. The determination of the research area and the determination of respondents were selected by purposive sampling. The results of this study indicate that; the total cost that must be incurred by the respondent farmers in each production or planting season is IDR 4,677,387.57 per hectare with a total income of IDR 23,009,120.37 per hectare. Based on the financial feasibility analysis, corn farming in Otak Rarangan Village is declared feasible, because it has an NPV value, Net B/C ratio, and Profitability Ratio greater than 0, and an IRR value greater than the applicable discount rate.